If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6(m-1m)=3(3m+5)
We move all terms to the left:
6(m-1m)-(3(3m+5))=0
We add all the numbers together, and all the variables
-(3(3m+5))+60=0
We calculate terms in parentheses: -(3(3m+5)), so:We get rid of parentheses
3(3m+5)
We multiply parentheses
9m+15
Back to the equation:
-(9m+15)
-9m-15+60=0
We add all the numbers together, and all the variables
-9m+45=0
We move all terms containing m to the left, all other terms to the right
-9m=-45
m=-45/-9
m=+5
| x+12=4x+13 | | -5.58+3.7k=16.99 | | -40=5(3x-2) | | 10x=25x5 | | 4q=14 | | x+3/4=5/10 | | 3(a-3)=-6a-(3a+9) | | –4/5(9x–20)–3x=45x–6 | | 15x=5x=25 | | 3x+12=4x-15 | | x²+14x=-46 | | z+4=10.47 | | 0.3(y+2=-6.3 | | x+7/9=5 | | 4(y-7)=7y-1 | | 3(2+5x)=x=3 | | 8(v−87)=96 | | -32=-2a+6 | | 5+4y=34 | | 1/2(c+1)=5 | | −3/1=j/4−3/10 | | 1=3+m/12 | | -5+10x=-2x+1 | | 5(2x+3)-x+8=13 | | −3/1=4j−3/10 | | -19x+5+12x=-3-7x+8 | | n÷13=11 | | 5(x)=4x-1 | | -9(x-6)=9x+108 | | |x|-10=-5 | | `-3x+15=-96` | | -11=4(w-8)+3w |